THE EFFECT OF DIFFERENT STOCKINGDENSITY ON THE GROWTH AND SURVIVAL RATE OF NILEM FISH (Osteochilushasselti) WITH RECIRCULATION SYSTEM - Mega Deswanti; Iskandar Putra; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research aims to determine the effect of differences in stocking density on the growth and survival of nilem fish (Osteochilus hasselti) using the recirculation system. The research container used was 12 aquariums measuring 60 x 40 x 40 cm. This study used an experimental method with one factorial completely randomized design, four treatments and three replications. The treatments applied were different stocking densities, namely P1 = 100 heads / m3 or 7 heads / 72 liters, P2 = 150 heads / m3 or 11 heads / 72 liters, P3 = 200 heads / m3 or 14 heads / 72 liters and P4 = 250 heads / m3 or 18 heads / 72 liters. The results showed that the treatment of different stocking densities in the recirculation system had a significant effect on the growth of nilem fish and the specific growth rate, but had no significant effect on feed conversion, blood glucose and the survival of the nilem fish seeds. The best treatment was P4 250 head / m3, which resulted in absolute weight growth (3.48 grams), absolute length growth (3.02 cm), specific growth rate (3.47%), feed conversion (1.50), blood glucose (82.33-84.33 mg / dL) and 90.74% survival rate. The quality of water during the research was obtained a temperature of 27-30oC, pH 6–7, (DO) 7,1 – 7,7 mg/L and ammonia 0,0004-0,0017 mg/L.Keywords:Nilem fish,Stocking density, Recirculation